A periodic meandering microstrip line leaky‐wave antenna with consistent gain and wide‐angle beam scanning. Issue 7 (22nd March 2022) - Wang, Henghui; Sun, Sheng; Xue, Xiaohan
Abstract: In this article, a periodic leaky‐wave antenna (LWA) with wide‐angle beam scanning and stable gain is proposed based on the meandering microstrip line. Due to the meandering property of the microstrip line, the longitudinal dimension of the antenna is reduced. Firstly, the radiation characteristic of the meandering microstrip line is analyzed in detail. Each corner of the meandering microstrip line is modeled by a shunt capacitance and shunt radiation conductance to acquire the equivalent circuit. Then, the frequency balanced condition is investigated based on the established equivalent circuit to realize continuous beam scanning through broadside. Subsequently, the method of open‐stop band (OSB) suppression is studied by introducing asymmetric perturbation on the LWA unit cell, which actually can be applied to eliminate the OSB effect in arbitrary symmetric LWAs. Finally, an antenna prototype is simulated and measured. The measured results agree well with the simulated results, validating the proposed method of OSB suppression. The measured results show that the designed antenna exhibits the beam scanning capacity of −47° to +76° with the frequency varying from 5.0 to 7.8 GHz and gain variation of 2.9 dB.